TREM2 protects against cerebral ischemia/reperfusion injury - Rong Wu (Molecular Brain, 2017)
Abstract Although post-ischemic inflammation induced by the innate immune response is considered an essential step in the progression of cerebral ischemia injury, the role of triggering receptor expressed on myeloid cells 2 (TREM2) in the pathogenesis of ischemic stroke remains to be elucidated. Here, we found that the transcriptional and post-transcriptional levels of TREM2 were increased in cultured primary microglia after oxygen-glucose deprivation and reoxygenation and in the ischemic penumbra of the cerebral cortex after middle cerebral artery occlusion (MCAO) and reperfusion in mice. TREM2 was mainly expressed in microglia, but not in astrocytes, neurons, or oligodendrocytes in mice subjected to MCAO. Manipulating TREM2 expression levels in vitro and in vivo significantly regulated the production of pro- and anti-inflammatory mediators after ischemic stroke. TREM2 overexpression markedly suppressed the inflammatory response and neuronal apoptosis. By contrast, TREM2 gene silencing intensified the inflammatory response, increased neuronal apoptosis and infarct volume, and further exacerbated neurological dysfunction. Our study demonstrated that TREM2 protects against cerebral ischemia/reperfusion injury through the aspect of post-ischemic inflammatory response and neuronal apoptosis. Pharmacological targeting of TREM2 to suppress the inflammatory response may provide a new approach for developing therapeutic strategies in the treatment of ischemic stroke and other cerebrovascular diseases.